Automated patient linking for electronic health record and child welfare databases. Issue 4 (2nd October 2019) - Dexheimer, Judith W.; Beal, Sarah J.; Divekar, Parth; Hall, Eric S.; Patel, Vikash; Greiner, Mary V.
Abstract: There are 427, 000 children in protective custody in the United States. A lack of integration between the child welfare data system and electronic health record systems complicates the communication of critical health history details to caregivers. We created and evaluated automated 10 custom algorithms linking these data. Deterministic matching was performed using combinations of first and last name, date of birth, and gender. If unmatched, a nondeterministic algorithm allowed for punctuation differences and letter transpositions. Of the children linked deterministically, 91.3% were linked. Of the ones undergoing nondeterministic matching, 71.3% were linked. Sharing integrated data is the first step in systematically improving health outcomes for children in protective custody. This approach represents an automatable and scalable solution that could help merge data from two disparate sources.